Designing the syllabus for the EAP course “Architectural Art English”: A needs and genre analysis-based approach - Rui Sun; Zhihao Chen (PLoS ONE, 2026)
This paper details the design and development of a discipline-specific English for Academic Purposes (EAP) syllabus for undergraduate students majoring in architecture and design related disciplines in an art school in China. Guided by the comprehensive needs analysis model established by Dudley-Evans and St. John [Developments in English for specific purposes: a multi-disciplinary approach. Cambridge University Press (1998)] and Swales [Genre analysis: English in academic and research settings. Cambridge University Press (1990)] genre theory, this study employed a university-wide questionnaire to gather data from 650 participants, including students and faculty. The needs analysis identified a critical disparity between students’ target academic aspirations—such as engaging in international collaboration, pursuing studies abroad, and understanding foreign lectures—and their present situational capabilities, particularly in listening comprehension and command of disciplinary vocabulary. In response to these findings, the proposed “Architectural Art English” syllabus is constructed around a genre-based, content and language integrated learning (CLIL) as well as task-based language teaching (TBLT) approach. It systematically incorporates seven key academic and professional genres relevant to the field: textbooks and monographs, research papers, case studies, and lecture scripts as input genres; and design statements, presentation scripts, and research abstracts as output genres. Each instructional unit is organized around a central architectural theme, utilizing authentic cases and genre analysis of move structures to make disciplinary discourse conventions explicit. The pedagogical framework emphasizes task-based learning, featuring authentic activities such as case analysis, design project presentations, and paper abstract writing to bridge the gap between language skills and disciplinary knowledge. This syllabus aims to addresses the complex interaction of learners’ target needs, subjective wants, and current proficiencies, facilitating their active participation in the global academic community of architecture and design.